Time Standards and Disability: A Work Measurement Perspective - Subramanian, Anand; Mital, Anil (International Journal of Industrial Engineering: Theory, Applications and Practice, 2022)
Traditionally, work measurement has been concerned with establishing consistent data on activity and job completion times for comparative, control, and/or remuneration purposes. The application of accurate work standards is not only crucial from the employees’ point of view but is also very important for the employers as it gives a measure of the productivity, and also standardizes the time it takes for businesses to produce its products or services. With changing demographics and growing need to include special population into the work force, it is necessary to analyze, modify, and implement the tried and tested approaches to productivity and performance measurement and improvement. This paper investigates the need to revise work standards in order to accurately determine levels of productivity and job completion times for the disabled. Specifically, the objectives of this paper are: a) to help practitioners understand the concept of a fair day’s work when it comes to the special disabled population; and b) to scrutinize the relation between published research on disability, work standards, and the need to customize them for the disabled population.